The immunogenic potential of bacterial flagella for Salmonella‐mediated tumor therapy. Issue 2 (7th January 2020) - Felgner, Sebastian; Spöring, Imke; Pawar, Vinay; Kocijancic, Dino; Preusse, Matthias; Falk, Christine; Rohde, Manfred; Häussler, Susanne; Weiss, Siegfried; Erhardt, Marc
Abstract : Genetically engineered Salmonella Typhimurium are potent vectors for prophylactic and therapeutic measures against pathogens as well as cancer. This is based on the potent adjuvanticity that supports strong immune responses. The physiology of Salmonella is well understood. It simplifies engineering of both enhanced immune‐stimulatory properties as well as safety features, thus, resulting in an appropriate balance between attenuation and efficacy for clinical applications. A major virulence factor of Salmonella is the flagellum. It is also a strong pathogen‐associated molecular pattern recognized by extracellular and intracellular receptors of immune cells of the host. At the same time, it represents a serious metabolic burden. Accordingly, the bacteria evolved tight regulatory mechanisms that control flagella synthesis in vivo . Here, we systematically investigated the immunogenicity and adjuvant properties of various flagella mutants of Salmonella in vitro and in a mouse cancer model in vivo . We found that mutants lacking the flagellum‐specific ATPase FliHIJ or the inner membrane ring FliF displayed the greatest stimulatory capacity and strongest antitumor effects, while remaining safe in vivo . Scanning electron microscopy revealed the presence of outer membrane vesicles in the ΔfliF and ΔfliHIJ mutants. Finally, the combination of the ΔfliF and ΔfliHIJ mutations with our previously described attenuated and immunogenic background strain SF102 displayed strong efficacy against the highly resistant cancer cell line RenCa. We thus conclude that manipulating flagella biosynthesis has great potential for the construction of highly efficacious and versatile Salmonella vector strains. Abstract : What's new? Owing to the ability of bacteria to elicit powerful immune responses, they are promising carriers for cancer‐targeting immunotherapies. However, balancing safety and therapeutic efficacy remains a major challenge for the rational design of bacteria for cancer immunotherapy. In the present study, the authors show that this balance can be achieved in Salmonella by manipulating the spatiotemporal regulation of flagella synthesis. Unexpectedly, abrogating flagella synthesis at an early stage resulted in outer membrane vesicle formation, which enhanced the bacterium's immunogenic properties. The engineered Salmonella strains reported here potentially can serve as vector platforms for various therapies, including immunizations and cancer treatments.